INDONESIAN MOTIVATION IN AGREES INDONESIA CHILE – COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IC-CEPA) AGREEMENT - Cika Ahdya Dewi Pratama; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Indonesia tries to improve its economic development. Latin America is a potential market for Indonesian products such as: footwear;tea,coffee, aluminium, seaweed, artificial flower and seafood. Chile as a develop country, a member of Organization for Economic Cooperation and Development (OECD) can be an access for Indonesian export. This research elaborated the reason why Indonesia elected Chile for cooperation through the Indonesia Chile - Comprehensive Economic Partnership Agreement (IC-CEPA).This explanative qualitative research is content analysis. Data from books, journals, official documents from Indonesian Ministry of Trade and Chilean Ministry of Foreign Affairs, Indonesian Ministry of Foreign Affairs, Indonesian Ministry of Finance, Indonesian Directorate General of International Trade Negotiations and websites from Indonesia Bank, CNN Business, IContainers, KBBI, Kumparan, Kontan, Republika, World Bank, and Wikipedia were utilized to analyzed phenomena of the cooperation and its progress. Theory of international cooperation from Dougherty &Pfaltzgraff about international cooperation explain cooperation between countries is not based on force and violence. Cooperation arises due to the commitment of individuals and the country to obtain collective welfare.The research showed that Chile is a strategic country in terms of location i.e. has borders with three big countries (Bolivia, Peru, and Argentina). Chile is a stable country based on Logistic Performance Index (LPI) level. Good facilities for international seaport and high purchasing power of Chilean. Complementary products between Indonesia and Chile became the push and full factors for cooperation. Indonesia Chile signed Indonesia Chile – Comprehensive Economic Partnership Agreement (IC-CEPA) on December 14, 2017 to accomplish the corporation. Activities have been conducted since August 10, 2019. Keywords: Motivation, IC-CEPA, Indonesia – Chile Agreement, Free Trade Area.